Gulag voices : an anthology - Applebaum, Anne, 1964- (Annals of Communism., 2011)
Collects the writings of a diverse group of people who survived imprisonment in the Gulag, recounting their experiences and relationships, and offering insight into the psychological aspects of life in the camps.